Comparative Analysis of Father and Son's Confrontation in Iranian and Greek Tragedies (Rostam and Esfandiar, Rostam and Sohrab and Oedipus Shahriar) - Hossein Mohammadi; Afsaneh Hassanzadeh Dastjerdi; Amir Abbas Azizifar (Matn/Pizhūhī-i Adabī, 2018)
The father and son's confrontation is one of the motifs seen in many myths, epics, legends, folk tales, or even in the religious narratives of the world. The background of this confrontation is generally the epic literary genre. In many of these confrontations, we encounter with tragedy. In this article, we have analyzed three stories of Oedipus Shahriar, Rostam and Esfandiar, and Rostam and Sohrab. The present research problem is that in epics those narrate these confrontations, although they have similar structures, according to the definition of tragedy, one who defeats and dies at the end of the Greek sample is father and in an Iranian sample is son. In response to this, we conclude that the background of ancient Greece's tragedy and its cultural structure, which is the result of democracy and dialogue in that culture, is the reason for the end in Greek example and the main reasons why the boy died in an Iranian sample, are binary oppositions, trying to keep the original sample, and the unicast mentality, in which another presence is denied.